Bridging the gap between clinical research evidence and practice : implementing the South African National Evidence-Based Asthma Guideline in Private and Public Practice in the Cape Metropole. - Pather, Michael Karl (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.